Study of rainfall-runoff relationship by using hydrologic modeling system (HEC-HMS) for Kuantan River Basin, Pahang - Nabilah, Mamat (2015)
River is important in human life. River is very useful and has various functions in human life such as for domestics, economics, connection for one place to other places and many more. The main function is the river is to flow the water to the water storage or sea. Landuse changes and urbanization has always been blamed as among the major causes of the increase in the magnitude and frequency flooding. Flash flood had occured in Kuantan River due to low lying of the draining area which the drainage capacity cannot cater the quantity of water when the capacity of runoff increases. When the quantity of the runoff is increasing and filled all the drainage and river, the flood will then occur. Therefore, this research aim is to carry out rainfall-runoff relationship for Kuantan River basin by using HEC-HMS, to apply the rainfall-runoff analysis by using Clark method in HEC-HMS and to determine discharge based on rainfall data. Relationship between rainfall and runoff will then be determined by the producing hydrograph from this software. In this software, hydrology parameter such as rainfall data and stream flow data are important to simulate rainfall-runoff data. In this study, HEC-HMS were used to develop hydrologic model for Sungai Kuantan basin based on the available data. The performance of determination correlation coefficient is used to measure the performance of the hydrologic modelling. From the simulated results, the maximum discharge was 286.3 m3/s during December 2011 at Bukit Kenau discharge station. The correlation coefficient for November 2011 was 0.9382 for Bukit Kenau discharge station. Approximately correlation coefficient to 1.0000 is better